A Top-Down Synthesis Route to Ultrasmall Multifunctional Gd-Based Silica Nanoparticles for Theranostic Applications - Mignot, Anna; Truillet, Charles; Lux, François; Sancey, Lucie; Louis, Cédric; Denat, Franck; Boschetti, Frédéric; Bocher, Laura; Gloter, Alexandre; Stéphan, Odile; Antoine, Rodolphe; Dugourd, Philippe; et al. (Chemistry : a European journal, 2013)
New, ultrasmall nanoparticles with sizes below 5 nm have been obtained. These small rigid platforms (SRP) are composed of a polysiloxane matrix with DOTAGA (1,4,7,10‐tetraazacyclododecane‐1‐glutaric anhydride‐4,7,10‐triacetic acid)–Gd3+ chelates on their surface. They have been synthesised by an original top‐down process: 1) formation of a gadolinium oxide Gd2O3 core, 2) encapsulation in a polysiloxane shell grafted with DOTAGA ligands, 3) dissolution of the gadolinium oxide core due to chelation of Gd3+ by DOTAGA ligands and 4) polysiloxane fragmentation. These nanoparticles have been fully characterised using photon correlation spectroscopy (PCS), transmission electron microscopy (TEM), a superconducting quantum interference device (SQUID) and electron paramagnetic resonance (EPR) to demonstrate the dissolution of the oxide core and by inductively coupled plasma mass spectrometry (ICP‐MS), mass spectrometry, fluorescence spectroscopy, 29Si solid‐state NMR, 1H NMR and diffusion ordered spectroscopy (DOSY) to determine the nanoparticle composition. Relaxivity measurements gave a longitudinal relaxivity r1 of 11.9 s−1 mM−1 per Gd at 60 MHz. Finally, potentiometric titrations showed that Gd3+ is strongly chelated to DOTAGA (complexation constant logβ110=24.78) and cellular tests confirmed the that nanoconstructs had a very low toxicity. Moreover, SRPs are excreted from the body by renal clearance. Their efficiency as contrast agents for MRI has been proved and they are promising candidates as sensitising agents for image‐guided radiotherapy. From the top down: Ultrasmall nanoparticles with a sub‐5 nm size have been synthesised by using a top‐down route. The nanoparticles are composed of a polysiloxane matrix holding Gd–DOTA chelates (DOTA=1,4,7,10‐ tetraazacyclododecane‐1,4,7,10‐tetraacetic acid). In rats, they have shown interesting properties as theranostic agents for radiosensitisation guided by magnetic resonance imaging.